2012
DOI: 10.1371/journal.pone.0031568
|View full text |Cite
|
Sign up to set email alerts
|

Blunted Neuronal Calcium Response to Hypoxia in Naked Mole-Rat Hippocampus

Abstract: Naked mole-rats are highly social and strictly subterranean rodents that live in large communal colonies in sealed and chronically oxygen-depleted burrows. Brain slices from naked mole-rats show extreme tolerance to hypoxia compared to slices from other mammals, as indicated by maintenance of synaptic transmission under more hypoxic conditions and three fold longer latency to anoxic depolarization. A key factor in determining whether or not the cellular response to hypoxia is reversible or leads to cell death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 54 publications
5
37
1
Order By: Relevance
“…The results from the calcium imaging experiments are consistent with this and, incidentally, the ability to load slice neurons from naked mole-rats with fura-2 far beyond weaning age is also highly suggestive (Peterson et al, 2012a). The 'neoteny hypothesis' for naked molerat brain also explains two other observations that we made in our initial studies of neuronal electrophysiology in hippocampal slices: a lack of synaptic (paired-pulse) facilitation and an insensitivity to exogenous adenosine -two features only observed in hippocampus of typical lab rodents very early in postnatal development (Larson and Park, 2009).…”
Section: Buried Alive! Arrested Development and Hypoxia Tolerance In supporting
confidence: 74%
See 2 more Smart Citations
“…The results from the calcium imaging experiments are consistent with this and, incidentally, the ability to load slice neurons from naked mole-rats with fura-2 far beyond weaning age is also highly suggestive (Peterson et al, 2012a). The 'neoteny hypothesis' for naked molerat brain also explains two other observations that we made in our initial studies of neuronal electrophysiology in hippocampal slices: a lack of synaptic (paired-pulse) facilitation and an insensitivity to exogenous adenosine -two features only observed in hippocampus of typical lab rodents very early in postnatal development (Larson and Park, 2009).…”
Section: Buried Alive! Arrested Development and Hypoxia Tolerance In supporting
confidence: 74%
“…6) . Evidence of blunted excitotoxicity and blunted calcium responses to glutamate is consistent with similar phenomena in the naked mole-rat (Peterson et al, 2012a;Peterson et al, 2012b). …”
Section: Resistance To Ischemia/reperfusion In the Euthermic State Insupporting
confidence: 74%
See 1 more Smart Citation
“…The results from the calcium imaging experiments are consistent with this and, incidentally, the ability to load slice neurons from naked mole-rats with fura-2 far beyond weaning age is also highly suggestive (Peterson et al, 2012a). The 'neoteny hypothesis' for naked molerat brain also explains two other observations that we made in our initial studies of neuronal electrophysiology in hippocampal slices: a lack of synaptic (paired-pulse) facilitation and an insensitivity to exogenous adenosine -two features only observed in hippocampus of typical lab rodents very early in postnatal development (Larson and Park, 2009).…”
Section: Buried Alive! Arrested Development and Hypoxia Tolerance In supporting
confidence: 74%
“…A key element of the hypoxia cascade that determines whether the cellular response is reversible or leads to cell death is the accumulation of free intracellular calcium ions, which trigger cytotoxic mechanisms (Deshpande et al, 1987; Lee et al, 1991). In a study using the calcium indicator, fura-2, we found that calcium accumulation during hypoxia is very much lower in brain slices from naked molerats compared with age-matched mice (Peterson et al, 2012a). Fig.…”
mentioning
confidence: 83%